A New Semi Analytical Method for Solving Some Non-Linear Infinite Boundary Value Problems in Physical Sciences - Subanya, R. R.; Ananthaswamy, V.; Sivasankari, S. (Communications in Mathematics and Applications, 2023)
One new approximate analytical method called Ananthaswamy-Sivasankari method for third order boundary value problems is applied to acquire the approximate solutions to some physical science problems, particularly Magnetohydrodynamic (MHD) casson fluid flow and MHD boundary layer flow analytically. The numerical and approximate analytical solutions to these equations are then compared and the results demonstrate a very good agreement. The resulting approximate analytical expressions are provided in an explicit and closed form. The outcomes demonstrated that the new approximate analytical method is more practical and simple to understand. Furthermore, a graphic interlining of the obtained findings is provided.